2019
DOI: 10.1007/s00221-019-05539-6
|View full text |Cite
|
Sign up to set email alerts
|

Rubber hands in space: the role of distance and relative position in the rubber hand illusion

Abstract: The rubber hand illusion (RHI) is a perceptual phenomenon in which participants experience ownership over a fake model hand through synchronous visuotactile stimulation. Several studies have shown that the illusion occurs only when both hands are in close proximity to each other. In the present study, we systematically examined the role of relative position (lateral, distal) and distance (13–75 cm) of the model hand (with respect to participants’ real hand) on illusion experience across both lateral and distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 43 publications
(85 reference statements)
3
31
1
Order By: Relevance
“…In fact, in both Experiments 1 and 2, the proprioceptive load felt at the shoulder and elbow would not arguably match the expected one, based on the visual modality (i.e., the position of the rubber hand). Our findings are in line with some (Kalckert et al, 2019;Lloyd, 2007;Preston, 2013), but not all (Abdulkarim & Ehrsson, 2016;Zopf et al, 2010) previous results. Overall, it is difficult to compare our results with those previously obtained because of the difference in the experimental setup used in each of these studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, in both Experiments 1 and 2, the proprioceptive load felt at the shoulder and elbow would not arguably match the expected one, based on the visual modality (i.e., the position of the rubber hand). Our findings are in line with some (Kalckert et al, 2019;Lloyd, 2007;Preston, 2013), but not all (Abdulkarim & Ehrsson, 2016;Zopf et al, 2010) previous results. Overall, it is difficult to compare our results with those previously obtained because of the difference in the experimental setup used in each of these studies.…”
Section: Discussionsupporting
confidence: 93%
“…It has also been suggested that the illusion would reduce because of the rubber hand being outside the peripersonal space around the subject's hidden hand (Preston, 2013). However, previous research has found mixed results in this regard (Kalckert, Perera, Ganesan, & Tan, 2019). Some authors have demonstrated that by increasing the distance between the two hands more than 30 cm, the illusion is not typically experienced (Kalckert & Ehrsson, 2014b;Lloyd, 2007), whereas others found the RHI to be robust against distance Roberto Erro and Angela Marotta contributed equally to this work.…”
mentioning
confidence: 98%
“…Importantly, we found a reduction in reported ownership when a rubber hand was placed 10 cm away from the real hand in the horizontal plane compared with 5 cm away. Such a spatial incongruency effect for a change in distance of only 5 cm between the seen rubber hand and the hidden real hand has not been detected in the earlier literature, where classical measurement methods were employed (Kalckert & Ehrsson, 2014;Kalckert et al, 2019;Lloyd, 2007;Motyka & Litwin, 2019;Preston, 2013;Zopf et al, 2010), and yet fits better with the high accuracy of individuals in perceiving the previously observed position of their arm (Paillard & Brouchon, 1968.;Walsh, Hesse, Morgan, & Proske, 2004). The more fine-grained spatial effect that could be revealed with the current psychophysics approach is more consistent with a multisensory account of body ownership because even small incongruencies between the seen and felt location of the hand should influence the integration of visual and somatic signals from the limb (van Beers, Sittig, & Gon, 1999;van Beers et al, 2002), and according to causal inference and optimal integration models of multisensory integration (Ehrsson & Chancel, 2019;Körding et al, 2007;Samad et al, 2015), any conflict between the sensory signals available to the participants, however minimal, should decrease the probability of them coming from the same source.…”
Section: Refining Knowledge Of the Spatial And Temporal Constraints Omentioning
confidence: 90%
“…It is also necessary to point out that, in general, we did not find differences in the sense of ownership between Congr and Incongr location of the hand/object. This might be due to the fact that, in this case, the Incongr location represented the position of the rubber hand in the typical RHI setting 9 , i.e., the hand was located in an anatomically plausible position and closer to the body midline than the real hand, and the distance between the hands was within the range that is considered suitable for inducing the illusion (e.g., 52,53 ). As in the RHI, such location allowed embodying the seen hand, and the strength of embodiment was similar to the Congr location.…”
Section: Discussionmentioning
confidence: 99%